Evaluation of Ankara Province Tobacco Control Inspectors’ Field Experiences and Opinions About Smoke-Free Airspace - Bulut, Yunus Emre; Erendur, Ebru; Ergüder, Toker; Çamur, Derya; Şirin, Hülya; Şimşek, Asiye Çiğdem; Hasde, Metin (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: This study was conducted to evaluate the field experiences of tobacco inspectors working in the smoke-free airspace implementation in Ankara Province and their opinions and suggestions on the development of smoke-free airspace implementation. Ankara Provincial/District Health Directorate‘s 77 tobacco control coordinators, tobacco inspectors, and clerical staff working in official correspondence between institutions participated in the study. The mean age of the participants was 44.36 ± 7.4 years (min: 24; max: 63); 61.0% (n = 47) were male, 49.4%(n = 38) were between the ages of 40 and 49, 53.2%(n = 41) were university graduates and above, and 33.8% (n = 26) were environmental health technicians. Of the participants, 81.9% stated that hookah cafes, 75.4% of traditional coffee houses/tea houses, 70.2% of bars/night clubs, and 66.3% of cafeterias/pastry shops have low compliance with the smoke-free airspace implementation, and 70.2%(n = 54) of the participants think that fines are generally useful, 59.7% (n = 46) emphasized camera recording of inspections, and 62.3%(n = 48) emphasized that the Green Detector application would facilitate the work of tobacco inspectors. Participants mentioned problems such as unclear definition of outdoor and indoor areas, insufficient knowledge of enterprises and the public about legal regulations, limited number of tobacco inspection teams, safety concerns of inspectors, and lack of technical infrastructure. They also suggested assigning inspectors from different institutions to the inspection teams, making fines more deterrent, increasing the authority of inspectors to impose fines, reviewing the licenses of establishments where tobacco is sold and served, aggravating the conditions for obtaining licenses, and increasing security measures.